Spatial and temporal characteristics analysis for land subsidence in Shanghai coastal reclamation area using PS-InSAR method - Li, Dong; Li, Bin; Zhang, Yuxin; Fan, Chao; Xu, He; Hou, Xiyong (Frontiers in Marine Science, 2022)
In recent decades, large-scale reclamation projects have been performed in the intertidal flat area of Shanghai, China. Due to the self-weight consolidation of the foundation and dynamic load caused by human activities, the newly reclamation area will sink within a period of time after the land is formed. Therefore, it is necessary to carry out surface deformation monitoring for taking preventive measures in advance. In this research, the PS-InSAR technology, mostly used for urban subsidence monitoring, was applied to obtain the ground deformation information of Shanghai coastal area based on ENVISAT/ASAR (2007.07-2010.02) and Sentinel-1A (2017.07-2020.02) datasets. The results showed that: 1) Compared with ASAR data, the Sentinel-1A data could distinguish more coherent points and get more comprehensive deformation distribution characteristics. 2) Most high-coherent points were detected in artificial objects, especially airport runways, buildings, roads and seawalls. 3) There was obvious uneven land subsidence in the study area during the two monitoring periods, the PS points with high subsidence rates (<-20 mm/a) mainly distributed around Dishui Lake and artificial seawalls. 4) The ground subsidence velocity of the newly formed land gradually slowed down over times, with the average subsidence rate decreased from -10.45 mm/a to -4.94 mm/a. Our study proved that remote sensing monitoring for ground subsidence in reclaimed land could be realized based on PS-InSAR technology, which could provide the spatial distribution characteristics of subsidence in large-scale and long-term series and help the sustainable development of coastal engineering construction.